Does women’s intra-household bargaining power have effect on child welfare? Evidence from farm households in Ogun state, Nigeria - Chioma Patricia ADEKUNLE; David Alaba ALORI; Adebayo Augustine KUTU (Acta Agriculturae Slovenica)
This study examines whether greater women’s household bargaining power is associated with the improvement in children’s welfare in Ogun State, Nigeria. Using data from 320 farm households with a Logit regression model, the study revealed that 31.86 % of children under-five years of age were stunted, 32 % were underweight and 16.2 % were wasted. Children growing up healthy were 62 %, implying that one – third of under-five children in the study area still experience nutrition deficiency. About 3.33 % and 1.05 % children simultaneously experienced stunting and wasting together, which perhaps suggests a harsh deprivation environment. In addition, 63.33 % of women in the study area had low bargaining power implying that they lack control over important decisions in their households. Women who enjoy decision-making power in their households, particularly with large purchasing power, are associated with having children with better height-for-age, mass-for-age, and mass-for-height ratios. Women’s inequality as relates to intra-household bargaining power negatively affects children’s welfare and leads to chronic malnutrition. As a policy recommendation, it is therefore, important to enhance women’s status, which, with time will lead to more investment in their children’s education, health, and overall welfare.